Endomicroscopy and Cancer: A New Approach to the Visualization of Neoangiogenesis. (12th January 2012) - Cannizzaro, Renato; Mongiat, Maurizio; Canzonieri, Vincenzo; Fornasarig, Mara; Maiero, Stefania; De Re, Valli; Todaro, Federico; De Paoli, Paolo; Spessotto, Paola
Abstract : Probe-based Confocal Laser Endomicroscopy (pCLE) is a novel imaging technique for gastrointestinal endoscopy providing in vivo microscopy at subcellular resolution. It offers the possibility to analyze neoangiogenesis and vessel density in vivo . Angiogenetic switch is essential in cancer progression. Aim of the paper was to review the use of this imaging tool to analyze colorectal and gastric cancers vascularization in vivo . The aim is to provide the possibility of combining diagnostic evidences with vascularization and molecular profile to evaluate the efficacy of an antiangiogenic treatment in association with conventional therapy. pCLE can be considered a revolutionary method for real-time assessment of changes in vascularization pattern in this tumors and it may open the possibility to address the use of anti-angiogenic therapy in order to improve the outcome of the treatment.